ATTITUDES OF FEMALE STREET VENDORS TOWARDS HIV/AIDS IN VHEMBE DISTRICT OF SOUTH AFRICA - Olaniyi, FC; Tshitangano, TG; Tugli, AK; Amosu, AM; Edokpayi, JN (African Journal of Infectious Diseases (AJID), 2017)
Background: The Human Immunodeficiency Virus (HIV) and Acquired Immunodeficiency Syndrome (AIDS) are still global health problems. This study was conducted to describe the attitudes of female street vendors (FSV) in Thohoyandou, Vhembe district, towards HIV/AIDS and those infected with the virus. Materials and methods: A quantitative, cross-sectional survey design was adopted. Data were collected by means of a structured, self-administered questionnaire and analyzed using the Statistical Package for Social Sciences (SPSS) version 20.0. Results: Majority (85.0%) of the participants had completed secondary education, 46.7% were single and 41.5% were aged 40 and above. Most of them (90.5%) indicated that they would accept to do a voluntary HIV test. Fear of stigmatization ranked highest among the reasons given by those not in favour of testing. Whilst 91.0% of the participants reported that they can stay in the same house with a person who is HIV positive and 88.5% said they would not have sex in exchange for money, only 57.5% indicated that they would agree to take antiretroviral drugs if they tested positive in pregnancy. The level of education was found to be significantly associated (p-value = 0.000) with the type of attitude shown towards HIV and those infected. Conclusion: It is recommended that HIV information providers and health workers in South Africa pay more attention to enlightening women about the importance of taking antiretroviral drugs in pregnancy to reduce the incidence of mother-to-child transmission of HIV.